Imaging of electric failure in Si-alloy/graphite-blended anodes for Li-ion batteries - Kang, Chansoon; Cho, Young Whan (ELSEVIER, 2021)
A new approach for detecting localized electrically failed particles in an electrode for Li-ion batteries (LIBs) in scanning electron microscope (SEM) is introduced to investigate the critical factor for the capacity fading of Sialloy/graphite-blended anodes. The present study proposes straightforward techniques for diagnosing failure commonly called the voltage contrast image (VCI) consist of two different methods, the passive voltage contrast (PVC) and the active voltage contrast (AVC). These methods widely used in semiconductor industries can be successfully adapted to the electrode degradation analysis for LIBs. These methods directly indicate electron charging effect on electrically disconnected particles caused by mechanical crack or the organic solid electrolyte interphases the mechanisms of capacity fading during the cycle while electrodes are being observed by SEM. The VCI results of the Si-alloy/graphite-blended anodes, particularly focusing on graphite particles, show that graphite particles near the current collector tend to be isolated individually whereas ones away from current collector keep their connectivity. These results give insights that which part should be improved to develop battery performance.
Keywords: GRAPHITE-ELECTRODES; HIGH-CAPACITY; SILICON; DEGRADATION; BEHAVIOR; STORAGE; CELLS